2014
DOI: 10.1128/jcm.03289-13
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of Ambiguous Base Calls in HIV-1 pol Population Sequences as a Biomarker for Identification of Recent Infections in HIV-1 Incidence Studies

Abstract: An increase in the proportion of ambiguous base calls in HIV-1 pol population sequences during the course of infection has been demonstrated in different study populations, and sequence ambiguity thresholds to classify infections as recent or nonrecent have been suggested. The aim of our study was to evaluate sequence ambiguities as a candidate biomarker for use in an HIV-1 incidence assay using samples from antiretroviral treatment-naive seroconverters with known durations of infection (German HIV-1 Seroconve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
17
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(18 citation statements)
references
References 29 publications
(75 reference statements)
1
17
0
Order By: Relevance
“…Kouyos et al [18] showed that time since infection correlated with the fraction of polymorphic nucleotides in partial HIV-1 pol gene sequences determined by Sanger sequencing. Others have later reported similar findings [1921]. This idea was expanded to other measures of sequence diversity, such as mean Hamming distance [6, 7, 22] and high-resolution melting (HRM) [23].…”
Section: Introductionmentioning
confidence: 87%
“…Kouyos et al [18] showed that time since infection correlated with the fraction of polymorphic nucleotides in partial HIV-1 pol gene sequences determined by Sanger sequencing. Others have later reported similar findings [1921]. This idea was expanded to other measures of sequence diversity, such as mean Hamming distance [6, 7, 22] and high-resolution melting (HRM) [23].…”
Section: Introductionmentioning
confidence: 87%
“…Ethics statement. The studies were approved by the data protection officer of the RKI and the German Federal Commissioner for Data Protection and Freedom of Information (III-401/008#0016) as well as the ethical committee of the Charité University Medicine (Berlin, Germany; EA 2/105/05) (19,50).…”
Section: Methodsmentioning
confidence: 99%
“…Although not perfect, the BED test is still the STARHS method used most frequently worldwide and has performed well in several recent studies. In a recent study performed on 1,334 seroconverters from German HIV‐1 Seroconverter Cohort, the BED test thus achieved a significantly higher accuracy than the sophisticated sequence ambiguity method using a 0.5% threshold (accuracy 84.6 vs. 75.5%, P < 0.001) [Meixenberger et al, ]. In combination with high‐resolution melting diversity, which does not require sequencing, the BED test also performed well in a recent study on samples from three large cohorts in the United States [Cousins et al, ], as well as in combination with an avidity assay (with and without CD4 and viral load testing) on 5,325 samples from seven large African cohorts [Laeyendecker et al, ].…”
Section: Discussionmentioning
confidence: 99%